Comparative Transcriptomic Analyses of Anthocyanin Biosynthesis Genes in Eggplant Under Low Temperature and Weak Light - Baoying Shen; Hongqi Wu; Xinxin Xie; Bo Zhao; Peiqiang Chen; Deyong Ao; Heli Pan; Biying Lin (Plants)
Low temperature, weak light, and the combination of low temperature and weak light can have an impact on the growth, development, and quality of eggplants. The color of the eggplant peel is affected by the anthocyanin content. To better understand the influence of low temperature, weak light, and the combination of low temperature and weak light on the regulation of anthocyanins in the eggplant peel, four treatments were carried out on the eggplants, respectively: low temperature (18/13 °C, 250 μmol/(m2·s)), weak light intensity (WL, 25/20 °C, 120 μmol/(m2·s)), low temperature combined with weak light intensity (LW, 18/13 °C, 120 μmol/(m2·s)), and the control (CK, 25/20 °C, 250 μmol/(m2·s)). The effects of low temperature and weak light on the anthocyanin content in various parts of the eggplant were analyzed, and transcriptome analysis was performed on the eggplant peel under the treatments of low temperature, weak light, and the combination of low temperature and weak light using RNA sequencing. The anthocyanin content in eggplants increased under low temperature and the combination of low temperature and weak light treatments, while it decreased under weak light. KEGG analysis showed that three pathways, namely phenylpropanoid biosynthesis, flavonoid biosynthesis, and anthocyanin biosynthesis, were involved in the anthocyanin biosynthesis of eggplants. Pearson correlation coefficients indicated that the anthocyanin content in the eggplant peel under low temperature and the combination of low-temperature and weak-light treatments was significantly correlated with SmPAL, Sm4CL, SmCYP73A100, SmCHS, SmCHI, F3H, DFR, ANS, and 3GT, and also significantly correlated with MYB, bHLH, and AP2/ERF. Under low-temperature and the combination of low-temperature and weak-light stress, the anthocyanin content increased due to the significant down-regulation of 3GT.